2019
DOI: 10.1161/atvbaha.119.312434
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Cells Contribute the Majority of Foam Cells in ApoE (Apolipoprotein E)-Deficient Mouse Atherosclerosis

Abstract: Objective— Smooth muscle cells (SMCs) are the most abundant cells in human atherosclerotic lesions and are suggested to contribute at least 50% of atheroma foam cells. In mice, SMCs contribute fewer total lesional cells. The purpose of this study was to determine the contribution of SMCs to total foam cells in apolipoprotein E-deficient (ApoE −/− ) mice, and the utility of these mice to model human SMC foam cell biology and interventions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
207
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(253 citation statements)
references
References 44 publications
16
207
0
Order By: Relevance
“…Yaa lupus-prone mouse is an increase in circulating monocyte counts which could explain the observed increase in plaque macrophages, without affecting plaque size 26 . Consistently, recent publications have shown that more than 50% of foam cells responsible for lipid deposition in the plaque arise from a phenotypical switch of smooth muscle cells 37 . However, the accumulation of macrophages can result in the build-up of uncleared apoptotic bodies, an important source of autoantigens and inflammation which in turn can promote plaque destabilization.…”
Section: Discussionsupporting
confidence: 72%
“…Yaa lupus-prone mouse is an increase in circulating monocyte counts which could explain the observed increase in plaque macrophages, without affecting plaque size 26 . Consistently, recent publications have shown that more than 50% of foam cells responsible for lipid deposition in the plaque arise from a phenotypical switch of smooth muscle cells 37 . However, the accumulation of macrophages can result in the build-up of uncleared apoptotic bodies, an important source of autoantigens and inflammation which in turn can promote plaque destabilization.…”
Section: Discussionsupporting
confidence: 72%
“…It should be noted that, while in humans foam cells are mainly derived from macrophages, [ 34 ] it has recently been discovered that foam cells can be derived from smooth muscle cells in the ApoE −/− mouse model. [ 35 ] Since the aforementioned studies and the study presented here are performed in LDLr −/− mice, it is unknown whether the therapeutic effect would be the same in ApoE −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV1 can also reduce aortic lipid accumulation and reduce foam cell formation. Foam cells derived from SMCs are the most abundant cells in human atherosclerotic lesions, accounting for at least 50% of the atherosclerotic lesion cells [21,22]. VSMCs express many cholesterol uptake receptors and reverse cholesterol transporters, including LDL receptor-related protein 1 (LRP 1), ATP binding box transporter A1 (ABCA 1) and low-density lipoprotein (LDL) receptor [23,24].…”
Section: Regulation Of Lipid Metabolismmentioning
confidence: 99%